Remarkable response to alectinib for metastatic papillary thyroid cancer with STRN-ALK fusion: A case report - Lucheng Zhu; Lucheng Zhu; Shenglin Ma; Bing Xia; Bing Xia (Frontiers in Oncology, 2022)
Little is known about the efficacy of alectinib for papillary thyroid cancer with STRN-ALK fusion. A 64-year-old female presented with metastatic papillary thyroid cancer, widespread to lungs, mediastinal lymph nodes and brain 20 years after surgery. Disease progression still occurred after radioactive iodine therapy, chemotherapy, and radiotherapy. Tissue obtained from left cervical lymph node confirmed metastatic papillary thyroid cancer. Molecular profiling from re-biopsy tissue identified an STRN-ALK fusion rearrangement. After multidisciplinary discussion, alectinib was administered to the patient. Treatment was well tolerated, and follow-up images confirmed a partial response. ALK occurs rarely, with limited data suggesting the efficacy of ALK inhibitors in thyroid cancer. We presented the first case of a patient with PTC and STRN-ALK fusion to be treat effectively with alectinib.